Analysis of Emotional Support for the Prevention of Sexual Harassment in High Schools - Andi Arisal; Arman Bin Anuar; Marhani Marhani (Educational Guidance and Counseling Development Journal, 2026)
Sexual harassment in schools endangers students' right to learn in a safe setting. This study aims to (1) identify essential aspects of emotional support that help prevent sexual harassment and (2) explore the relationship between students’ perceived emotional support and their ability to respond to such incidents. Using a quantitative correlational approach, the research sampled 304 students from public high schools in Palopo City through quota sampling. Data were gathered via a Likert-scale questionnaire and analyzed using descriptive and inferential statistics, including tests for validity, reliability (Cronbach's Alpha), normality, linearity (ANOVA), and Spearman Rank correlation. Results reveal that emotional support from teachers, peers, and the school environment plays a crucial role in fostering a sense of security and mitigating sexual harassment. The instrument demonstrated adequate reliability (Cronbach's Alpha = 0.752). Although the data were non-normally distributed (Sig. < 0.05), the relationship between variables remained linear. Spearman’s correlation indicated a coefficient of 0.452 with a significance level of 0.000 (< 0.05), highlighting the positive effect of emotional support on preventing sexual harassment in schools. Kata kunci: emotional support, sexual harassment prevention, school.